Comparative efficacy of low-dose versus regular-dose colchicine to prevent flares in gout patients initiated on urate-lowering therapies. (25th March 2021) - Ahn, Soo Min; Oh, Ji Seon; Hong, Seokchan; Lee, Chang-Keun; Yoo, Bin; Kim, Yong-Gil
Abstract: Objective: The objective of this study was to compare the prophylactic effect of regular-dose (RD, 1.2 mg/day) vs low-dose (LD, 0.6 mg/day) colchicine on gout flare when initiating urate-lowering therapy. Methods: In this retrospective cohort study, we included gout patients who were initiated on either allopurinol or febuxostat, in combination with colchicine therapy and followed them up for 3 months. We analysed the rates of gout flare and adverse events according to the dose of colchicine. We performed the inverse probability of treatment weighting (IPTW) and weighted logistic regression analysis to assess the treatment effect. Analysis of gout flares and adverse events was performed on an intention-to-treat (ITT) and per-protocol (PP) basis. Results: Of the total of 419 patients with gout, 177 patients (42.2%) received LD colchicine, whereas 242 patients (57.8%) received RD colchicine. Lower BMI and estimated glomerular filtration rate, and higher incidence of cardiovascular disease were seen in the LD group than in the RD group. In IPTW-adjusted analysis, events of gout flare were not significantly different between the LD and RD groups [ITT: 14.3% vs 11.3%; odds ratio (OR): 1.309, 95% CI: 0.668, 2.566, P  = 0.432; PP: 15.3% vs 10.0%; OR: 1.623, 95% CI: 0.765, 3.443, P  = 0.207]. However, LD colchicine was associated with a lower rate of adverse events than RD colchicine [ITT: 8.2% vs 17.9%; OR: 0.410, 95% CI: 0.217, 0.777; P  < 0.05; PP: 8.4% vs 17.2%; OR: 0.442, 95% CI: 0.223, 0.878; P  < 0.05]. Conclusion: Our data suggest that LD colchicine can adequately prevent gout flare with fewer adverse events compared with RD colchicine.